Optimalisasi Sistem Manajemen Lingkungan yang Terintegrasi Melalui Penerapan Balanced Scorecard - M.Rosidi Tarigan; Dwi Nowo Martono; Umanto (Universitas Negeri Jakarta, 2021)
The ISO 14001 environmental management system has been implemented by many types of organizations, but there are still many differences of opinion related to the effectiveness of the implementation of this standard on improving environmental performance in an organization. The effectiveness of the implementation of environmental management system standards is highly dependent on strategic planing gaps with other management systems integrated in an organization. The balanced scorecard concept has provided a comprehensive framework for translating the company's strategic planning into more comprehensive performance measurement. To analyze the condition of strategic planing in an integrated management system that has adopted the concept of a balanced scorecard at PT. Xyz, researchers used a descriptive analysis method, the results obtained that strategic planning in 2014, 2015 and 2018 have coherence, but in 2016-2017 it is not coherent, which means that strategic planning starts not in accordance with the attributes of the balanced scorecard concept. Correlation test method is used to analyze the effect of strategic planning with environmental performance and economic performance at PT. Xyz, the results obtained that strategic planning in an integrated management system that adopts a balanced scorecard has a positive effect on environmental performance but does not have a positive effect on economic performance. Strategic planning interventions through the formulation of corporate strategy using the DEMATEL method obtained corporate strategy impact relations map which formulates the six criteria of the most priority corporate strategy recommendations for improving environmental performance and economic performance at PT. Xyz in the future